2020
DOI: 10.1177/1479164120958422
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow impairment in asymptomatic patients with early stage type-2 diabetes: Detection by FFRCT

Abstract: Purpose: To determine the occurrence of physiological significant coronary artery disease (CAD) by coronary CT angiography (CTA) derived fractional flow reserve (FFRCT) in asymptomatic patients with a new diagnosis (<1 year) of type-2 diabetes mellitus (T2DM). Methods: FFRCT-analysis was performed from standard acquired coronary CTA data sets. The per-patient minimum distal FFRCT-value (d-FFRCT) in coronary vessels (diameter ⩾1.8 mm) was registered. The threshold for categorizing FFRCT-analysis as abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…In contrast to the current analysis, the abnormal FFR-CT ≤ 0.75, which is indicative of hemodynamic significant lesion, is associated with low-attenuation non-calcified plaques which is an established marker of high risk vulnerable plaque and has been predictive of adverse cardiac events in DM patients. [ 25 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the current analysis, the abnormal FFR-CT ≤ 0.75, which is indicative of hemodynamic significant lesion, is associated with low-attenuation non-calcified plaques which is an established marker of high risk vulnerable plaque and has been predictive of adverse cardiac events in DM patients. [ 25 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…showed that diabetes has no negative impact on the diagnostic accuracy of machine learning-based C FFR [32] . Especially patients with type two diabetes mellitus have a high burden of CAD already in an early stage of the disease, and an advantage from hemodynamic evaluation of significant CAD by C FFR is proven [33] .…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…FFR-CT is an alternative functional technique, which combines anatomic and physiologic information in a single non-invasive test. Patients with diabetes have a high burden of coronary artery disease and it has been shown that every sixth asymptomatic patient at the time of the diagnosis of diabetes has haemodynamically significant plaque disease as evaluated by FFR-CT ( 44 ) (see an example of FFR-CT assessment in Figure 1 ). FFR-CT has improved specificity without impacting on the sensitivity of CTA in detecting haemodynamic significant coronary artery disease ( 45 ).…”
Section: The Role Of Coronary Ct In the Management Of Coronary Artery...mentioning
confidence: 99%